Study on the Relationship between Storage Conditions and Quality Changes of High-quality Indica Rice - Zaixi SHU; Yifan CHEN; Wei ZHANG; Pingping WANG; Huang DAI (Shipin gongye ke-ji, 2022)
In order to explore the relationship between storage conditions and the quality changes of high-quality indica rice, the high-quality indica rice “Fengyou 22” samples were stored at 4 storage temperatures (15, 20, 25 and 30 ℃) and 3 moisture contents (13.5%, 14.5% and 15.5%) and 2 gas composition (modified atmosphere with nitrogen, non-modified atmosphere) simulated storage for 360 d, and the yellow rice content, germination rate, electrical conductivity, α-amylase activity, fatty acid value, gel consistency, straight chain starch content, rice soup solids, iodine blue value and rice hardness, rice viscosity, rice balance, rice elasticity, appearance score, taste score, comprehensive score and other indicators were regularly determined. The results showed that the higher the storage temperature and the higher the moisture content, the more obvious the quality changed; under the same condition of storage temperature and moisture content, nitrogen storage had the effect of delaying the quality change. The principal component analysis method was used to analyze the 16 indicators, and 5 principal component factors with a cumulative contribution rate of 81.055% were obtained through dimensionality reduction. Representative quality indicators were chosen from the indicators with larger positive eigenvalues in each principal component, which were germination rate, electrical conductivity, iodine blue value and amylose content. The correlation analysis of the four characteristic indexes with storage temperature, moisture content and gas composition showed that storage temperature had the greatest influence on the characteristic indexes of high-quality indica rice, followed by moisture content then gas composition.